A LEVEL OF ASSURANCE OF SELF–DEFENCE INSTRUCTORS FOR WORKING WITH PEOPLE WITH SPECIFIC GROUPS - Alena Skotáková; Jitka Čihounková; Andrea Martincová (The Sky, 2022)
The number of attacks on people with different types of special needs worldwide is growing. It causes the increasing request for self-defence courses created for a group of people with disabilities. Most self-defence systems dealing with specific groups focus on women or elderly people. People with disabilities are least included. The aim of this research was to find how self-defence instructors feel prepared to work with specific groups, including people with disabilities. This research involved 65 respondents (52 men and 13 women). Self-assessment of the ability and willingness to lead, communicate or organise self-defence courses for individual groups with special needs or willingness to integrate these people into regular self-defence lessons were evaluated by a created questionnaire. Results showed that self-defence instructors are most concerned about working with people with mental impairments and do not feel well trained or prepared to work with specific groups, except for self-defence of women, children, and seniors. For improvement, self-defence instructors require a level of self-assurance for working with people with special needs. This will require targeted education aimed at working with people with disabilities.